Contour-solid properties of finely holomorphic functions - Sarana, A. A.; Tamrazov, P. M. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
We prove contour-solid theorems for holomorphic functions defined in finely open sets of the complex plane.